2020
DOI: 10.1002/gj.3980
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the understanding of the Pinheiro Machado Complex (Dom Feliciano Belt, Brazil): A study of textures, mineral chemistry, and crystallization conditions

Abstract: This article presents textures, mineral chemistry, and geothermobarometric data for the southeastern Pinheiro Machado Complex rocks (PMC), eastern domain of the Dom Feliciano Belt, Rio Grande do Sul, Brazil. The PMC is composed by comagmatic intrusions of quartz diorite, tonalite, and granodiorite with medium‐ to fine‐grained equigranular and medium‐grained inequigranular textures with subordinate alkali‐feldspar macrocrystals. Partial melting features are observed in the comagmatic as melt pools and melt film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 65 publications
1
9
0
1
Order By: Relevance
“…The PMC comprises plutonic rocks with a wide compositional range along a northeast‐southwest trending belt in the southeastern region of the Pelotas Terrane. Bastos et al (2021) investigated the crystallization conditions of the PMC rocks and demonstrated multiple pulse magmatism besides other important mechanisms, which was confirmed by Loureiro et al (2021), who described the studied area as a result of multi‐intrusive pulses subdivided into distinct magmatic phases.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…The PMC comprises plutonic rocks with a wide compositional range along a northeast‐southwest trending belt in the southeastern region of the Pelotas Terrane. Bastos et al (2021) investigated the crystallization conditions of the PMC rocks and demonstrated multiple pulse magmatism besides other important mechanisms, which was confirmed by Loureiro et al (2021), who described the studied area as a result of multi‐intrusive pulses subdivided into distinct magmatic phases.…”
Section: Introductionmentioning
confidence: 73%
“…Slab rupture and failure are essential components of plate tectonics and a natural consequence of the subduction process (Davies & Von Blanckenburg, 1995;Sacks & Secor Jr, 1990). These processes include The processes of mixing, assimilation and hybridization are common evidence discussed by authors studying the PMC (Bastos et al, 2021;Cruz et al, 2023;Loureiro et al, 2021). Approaching a more regional context, Cruz et al (2023) describe these mixing processes and assimilation of country rocks, suggesting multi-stage magmatism related to episodes of intense magmatic peaks, potentially triggered by changes in the tectonic setting.…”
Section: Tectonic Settingmentioning
confidence: 97%
See 2 more Smart Citations
“…1B). Este embasamento é representado pelos ortognaisses Arroio Pedrado (idade de cristalização magmática datada em 680 Ma), interpretados como remanescentes do Arco Piratini (Vieira et al, 2019b); as rochas meta-máficas-ultramáficas-sedimentares do Complexo Arroio Grande (800-600 Ma - Ramos et al, 2020); e os granitoides mais antigos do Complexo Pinheiro Machado (630-609 Ma -Philipp et al, 2002;Loureiro et al, 2015;Bastos et al, 2020). O magmatismo sin-cinemático principal relacionado às referidas zonas de cisalhamento da região de Arroio Grande resulta no alojamento do granito peraluminoso Três Figueiras (Klein et al, 2018;Vieira et al, 2021) e no Granito Chasqueiro (Vieira et al, 2016), foco do presente estudo.…”
Section: Contexto Geológicounclassified